Improving Health Service Quality Management in Hospitals (Literature Study) - Dewi Agustina; Arini Fajriani; Alwi Safriansyah Lubis; Dina Anggreini; Fitri Amja Yani; Nyak Firzah (Majalah Kesehatan Indonesia, 2022)
Hospitals as the main goal of overcoming public health complaints should try to provide best quality services to patients from all walks of life. For this reason, it is necessary to have service quality management as a process of optimizing the implementation of health activities according to established health service standards. The research method used is a literature study method related to a series of activities related to the collection of library data regarding improving the quality management of health services in hospitals that are sourced from research journals that will be read, writtten, and then the datas will be processed. Quality management of health services in hospitals can be improved by paying attention to aspects of fulfilling hospital accreditation according to established standards, fulfilling hospital minimum service standards, implementing management functions in health programs such as BPJS Kesehatan, as well as analysing integrated quality management (TQM) and based on ISO 9001:2015